Policy on Strengthening the Role of Libraries in Supporting Scholarly Communication at IAIN Curup - Rizal, Syamsul; Rodin, Rhoni (Record and Library Journal, 2021)
Background of the study: Libraries occupy a very strategic position in supporting scientific communication in universities. Purpose: This study aims to analyze the policy of strengthening the role of libraries in supporting scientific communication at IAIN Curup. Method: This type of research is descriptive qualitative. Data collection was carried out by means of interviews and documentation. Findings: The results of this study indicate that there are several policies that have been and will be carried out by the IAIN Curup and the IAIN Curup Library in supporting scientific communication at IAIN Curup, namely 1) regulations and development strategies in the institutional strategic plan; 2) carry out routine user education activities; 3) online research skills training for academicians; 4) providing e-resources; 5) information literacy class program for students and lecturers; and 6) book review activities. The lecturers hope that the means of scientific communication can be improved so that the role of libraries can be maximized in scientific communication activities. The concept that can be offered in order to strengthen the role and function of libraries in the development of scientific communication at IAIN Curup is the revitalization of user education by adding facilities and facilities for user education activities. Then the increase in the promotion of services and facilities at the IAIN Curup Library. Conclusion: The position of libraries in supporting scientific communication in tertiary institutions must be strengthened through policies in favor of libraries.